Statistics for imaging, optics, and photonics - Bajorski, Peter 1958- (Wiley series in probability and statistics, 2012)
"This important resource bridges the gap between imaging, optics, and photonics, and statistics and data analysis. The text contains a wide range of relevant statistical methods including a review of the fundamentals of statistics and expanding into multivariate techniques. The techniques are explained in the context of real examples from remote sensing, multispectral and hyperspectral imaging, signal processing, color science, and other related disciplines. The book also emphasizes intuitive and geometric understanding of concepts. The topics that are most relevant to imaging, optics, and photonics applications are covered thoroughly. In addition, supplemental topics are discussed to provide an overview of when and how the methods can be used."